Implementasi Sistem Informasi Pemasaran Rumah Dengan Pendekatan Sistem Berorientasi Objek Pada Developer Property - Mustar - Aman; Riyanto .; Suroso .; Ipang Sasono; Yunianto Agung Nugroho (STMIK IKMI Cirebon, 2021)
Marketing in this century has developed quite rapidly and is in demand by business actors because it has promising opportunities, including in big cities such as Tangerang. Property developer is a property developer engaged in housing. Until now, the marketing system for property developers is how to sell as much housing as possible in one month. The problem that occurs in the marketing system at property developers is that it is not yet computerized or web-based because the home marketing process is still using the technique of distributing brochures and data processing so far it is still conventional and the list of booking lists and pricelists of house unit prices are not yet detailed. The purpose of the research is to build a housing unit marketing system using conceptual analysis and to find out what supporting and inhibiting factors are on property developers. The research method used is descriptive qualitative. Data collection techniques were carried out by means of observation, interviews and literature study. The results of this study are in the form of software, namely a web-based housing marketing system that can display detailed housing information including housing building specifications, price lists, housing locations, stock units, location maps and payment details